Hubungan Sikap dengan Perilaku Masyarakat terhadap Pencegahan Covid 19 di Kecamatan Karawaci Tahun 2020 - Ni Nyoman Yeni Puspita Sari; Zahra Maulidia Septimar (Jurnal Health Sains, 2021)
COVID-19 as a world problem in the health sector. At the same time, World Health Organizatin (WHO) said there were pneumonia cases in Wuhan, Hubei, China whose cause was unclear and it was increasingly spreading outside the country. After that, the World Health Organization, in this case the WHO, declared COVID-19 as a pandemic in March 2020. To determine the relationship between attitudes and community behavior in preventing the transmission of COVID 19 in Karawaci District, Tangerang City in 2020. This research method is descriptive analytic. with a cross sectional approach. Quota sampling technique, research sample of people living in Karawaci sub-district. Chi-square result. The relationship between attitude and community behavior is obtained p-value 0.000 <0.05, which means that there is a significant relationship between attitude and community behavior with very low relationship closeness. The results showed that there is a significant relationship between attitudes and community behavior. It is hoped that the community can maintain good attitudes and behavior in preventing transmission of COVID-19.